Aplicação de modelo para mapeamento de lacunas de percepção no negócio de e-procurement - Costa, Ernani Luiz Carvalho (2005)
The Business to Business solutions of the purchases automation through emarketplaces and especially the e-procurement system, it is considered as the system that assures the acquisition, payment, and administration of materials and services with a considerable decresase of the operational costs of the companies. The present work proposes a model for mapping the perception gaps among companies that disposes the e-procurement solution in Brazilian market. These mapping also alow it to identify the real levels of the customers satisfaction at e-procurement solution. This project represents an indicative demand of market and it makes possible an electric outlet of managerial decision in sense of minimizing the perception gaps between customers and suppliers at the e-procurement solution, whitout loss of the main focus, because improving investments can be better addressed to customers real needs